1987
DOI: 10.3109/10408448709089862
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Food Additive Migration from Polymeric Food Packaging Materials

Abstract: Many foods contact polymeric packaging materials which contain residues of the polymerization process or additives employed to facilitate processing. The extent of migration of such materials from the packaging to foods is the focus of the present article. A major experimental program using eight polymer-migrant systems is described. Migration was measured to food-simulating liquids (FSL) and to foods. Accelerated tests were conducted with FSL under FDA guidelines conditions so as to develop correlations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Till et al. () pointed out that time, temperature (related to whether or not polymer was above or below the Tg, glass transition temperature), migrant concentration, agitation, polymer morphology (thickness) and migrant type affected scalping. Fayouz et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Till et al. () pointed out that time, temperature (related to whether or not polymer was above or below the Tg, glass transition temperature), migrant concentration, agitation, polymer morphology (thickness) and migrant type affected scalping. Fayouz et al.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the lining polymers would be expected to have an impact on scalping rates and amounts. Till et al (1987) pointed out that time, temperature (related to whether or not polymer was above or below the Tg, glass transition temperature), migrant concentration, agitation, polymer morphology (thickness) and migrant type affected scalping. Fayouz et al (1997b) reported the free volume, crystallinity, polarity, tacticity, crosslinking, orientation (stretching), additives as well as the polymer blends affect rate of sorbtion of a given compound.…”
Section: Resultsmentioning
confidence: 99%
“…Chemicals migrate from all types of food contact materials and articles Chemicals can transfer from food contact materials and articles into food. This phenomenon is known as migration and has been studied since the 1950s [29][30][31][32][33]. All types of food contact materials may exhibit chemical migration, but the types of migrating chemicals and their levels differ significantly.…”
Section: Part 1 Facts Based On Established Scientific Data and Findingsmentioning
confidence: 99%
“…Surrogate test materials are commonly used in the evaluation of migration from food-contact materials (Till et al 1987). This representative test material could potentially be used as a surrogate model for determining the percentage of residual PFOA that may actually migrate from PTFE-coated cookware to food.…”
Section: Migration Of Pfoa From Ptfementioning
confidence: 99%